Kepadatan Populasi Ulat Penggerek Polong (Maruca testulalis) pada Tanaman Kacang Panjang (Vigna sinensis) di Kelurahan Gunung Sarik Kecamatan Kuranji Kota Padang - Alwasilah Yofita Ilham; Nurhadi; Elza safitri (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
The population of Maruca testulalis in the long bean (Vigna sinensis) can lower the yield productions. Maruca testulalis attack the part of the pods long bean that left little holes in the pod. In that regard, so the research has been done about population density Maruca testulalis on the long bean plant (Vigna sinensis) in Celebacy Gunung Sarik Seedlings Kuranji Padang City. This research has been done, in January-February 2019 by using Survey Descriptive method which is a direct collector of pods long beans. Purposive Random Sampling technique sample. Sample were taken at 60 days and 70 days. Measured environmental conditions thats temperature, humidity, precipitation, wind speed, and pH. Based on the research being done, population density Maruca testulalis on the long bean plant (Vigna sinensis) in Celebacy Gunung Sarik Seedlings Kuranji Padang City 1,3 individual/plant (age 60 days) and 0,95 individual/plant (age 70 days). Population density Maruca testulalis 1,12 individuals/plants and fall in the category of light attack.